Pola Tata Ruang Weltevreden dan Fungsi Ruang Kota - Iwan Hermawan; Octaviadi Abrianto (Kemendikbud, 2020)
The deterioration in the quality of health in Batavia and preparations for the British attack on Java in the early 19th century prompted the Governor of the Dutch East Indies, HW Daendels, to move the administrative center from Batavia to Weltevreden. Various central government facilities were built in Weltevreden. The problems discussed are related to the development of the urban spatial planning of Weltevreden as the center of government during the Dutch Colonial period. The aim is to uncover the development of Weltevreden’s urban spatial structure during the Dutch Colonial period. The method used is descriptive analysis with a spatial approach. The construction of Weltevreden as the center of government was carried out because the area was healthier than the old Batavia region. This area also developed into a center of community activity with its center in Waterlooplein.